The Influence of Product Quality, Price and Location on Consumer Purchase Decisions for Second Imported Clothing at Janeta Fashion Manna - Muhammad Abdullah; Nurzam Nurzam; Ida Ayu Made. E. G (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to determine the effect of product quality, price and location on consumer’s purchasing decisions of import preloved clothing at Janeta Fashion Manna. The sample in this study was taken as many as 10 consumers who made purchasing decisions for 7 days, therefore the total sample was 10 x 7 = 70 consumers. This research is quantitative research using non-probability technique with purpose sampling method. The instrument in this study was a questionnaire which was then processed using the SPSS version 26.0 computer application. The analytical method used is multiple linear regression analysis and hypothesis testing. The results showed that the results of the regression analysis obtained the equation Y= 22.910-0.159X1+0.443X2+0.087X3+4.709. The coefficient of determination is 0.241, which means that product quality, price and location affect purchasing decisions by 24.1%, while the remaining 75.9% is influenced by other variables not examined in this study. The results of the T test at a significance level of 0.05 explained that partially the product quality and location variables did not have a significant influence on the purchasing decision variables because the significance value was > 0.05. While the price variable has a significant influence on the purchasing decision variable because the significance value is <0.05. The results of the F test at a significance level of 0.05 explains that the variables of product quality, price and location have a simultaneous (together) effect on purchasing decisions because the significance value is <0.05.